2022
DOI: 10.3390/math10193566
|View full text |Cite
|
Sign up to set email alerts
|

A Wavelet PM2.5 Prediction System Using Optimized Kernel Extreme Learning with Boruta-XGBoost Feature Selection

Abstract: The fine particulate matter (PM2.5) concentration has been a vital source of info and an essential indicator for measuring and studying the concentration of other air pollutants. It is crucial to realize more accurate predictions of PM2.5 and establish a high-accuracy PM2.5 prediction model due to their social impacts and cross-field applications in geospatial engineering. To further boost the accuracy of PM2.5 prediction results, this paper proposes a new wavelet PM2.5 prediction system (called WD-OSMSSA-KELM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(1 citation statement)
references
References 79 publications
0
1
0
Order By: Relevance
“…After outlier correction, considering the inherent nonlinearity and noise characteristics of wind speed data, applying data decomposition techniques can effectively reduce the instability of wind speed time series and eliminate redundant information. Recent studies have shown that combining data decomposition methods with advanced machine learning models can significantly improve the accuracy of wind speed predictions [27,28]. For example, Liu et al [29] utilized wavelet decomposition to reduce the volatility of time series and LSTM to extract time series features, thus constructing a hybrid model combining Wavelet Decomposition (WD) and LSTM for forecasting.…”
Section: Related Workmentioning
confidence: 99%
“…After outlier correction, considering the inherent nonlinearity and noise characteristics of wind speed data, applying data decomposition techniques can effectively reduce the instability of wind speed time series and eliminate redundant information. Recent studies have shown that combining data decomposition methods with advanced machine learning models can significantly improve the accuracy of wind speed predictions [27,28]. For example, Liu et al [29] utilized wavelet decomposition to reduce the volatility of time series and LSTM to extract time series features, thus constructing a hybrid model combining Wavelet Decomposition (WD) and LSTM for forecasting.…”
Section: Related Workmentioning
confidence: 99%